For a translational sociology: Illuminating translation in society, theory and research. (August 2022) - Bielsa, Esperança
This article argues for a non-reductive approach to translation as a basic social process that shapes both the world that sociologists study and the sociological endeavour itself. It starts by referring to accounts from the sociology of translation and translation studies, which have problematized simplistic views of processes of cultural globalization. From this point of view, translation can offer an approach to contemporary interconnectedness that escapes from both methodological nationalism and what can be designated as the monolingual vision, providing substantive perspectives on the proliferation of contact zones or borderlands in a diversity of domains. The article centrally argues for a sociological perspective that examines not just the circulation of meaning but translation as a process of linguistic transformation that is necessarily embodied in words. Only if this more material aspect of translation is attended to can the nature of translation as an ordinary social process be fully grasped and its intervention in meaning-making activities explored. This has far-ranging implications for any reflexive account of the production of sociological works and interpretations.